Otogenic meningoencephalomyelitis due to Cryptococcus gattii (VGII) infection in a cat from Western Australia. Issue 1 (22nd May 2015) - Siak, Meng K; Paul, Amanada; Drees, Randi; Arthur, Ian; Burrows, Amanda K; Tebb, Anna J; Malik, Richard
Case summary: A 7-year-old spayed domestic longhair cat from Perth, Western Australia, presented with left-sided head tilt, dysphonia, head shaking, inappetence and weight loss. A polypoid lesion had previously been removed from the external ear canal. Otitis media with extension into the external ear canal was suspected and investigated using video-otoscopy and computed tomography examination. Invasive disease with extension from the middle ear to the base of the skull, and intracranial extension into the caudal fossa and cranial cervical vertebral canal was detected. Cytology of external ear canal exudate showed capsulated budding yeasts and Cryptococcus gattii VGII was cultured. Treatment with amphotericin B infusions and oral fluconazole was prescribed, with nutritional support via oesophagostomy tube. The cat clinically recovered 12 months after treatment commenced. Relevance and novel information: This case report describes the successful medical treatment of otogenic meningoencephalomyelitis due to C gattii (VGII) infection in a cat.